2000
DOI: 10.1016/s0022-2275(20)32052-6
|View full text |Cite
|
Sign up to set email alerts
|

Plasma 24S-hydroxycholesterol (cerebrosterol) is increased in Alzheimer and vascular demented patients

Abstract: Alzheimer's disease (AD) is characterized by the presence of senile plaques, neurofibrillary tangles, and neuronal cell loss associated with membrane cholesterol release. 24S-hydroxycholesterol (24S-OH-Chol) is an enzymatically oxidized product of cholesterol mainly synthesized in the brain. We tested the hypothesis that plasma levels of this oxysterol could be used as a putative biochemical marker for an altered cholesterol homeostasis in the brain of AD patients. Thirty patients with clinical criteria for AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 341 publications
(58 citation statements)
references
References 19 publications
3
49
1
5
Order By: Relevance
“…As the expression of cholesterol (24S)-hydroxylase is mainly localized to neuronal cells, and (24S)-hydroxycholesterol is mainly located in myelin, an expected consequence of active neurodegeneration would be a transient increase in the flux of (24S)-hydroxycholesterol across the blood-brain barrier. In support of this hypothesis we have observed slightly but significantly increased levels of circulating (24S)-hydroxycholesterol in a specific population of Alzheimer patients (19). In advanced neurodegeneration the decrease in neuronal mass could result in a reduced flux of (24S)-hydroxycholesterol, and we have observed a negative correlation between mental capacity and circulating levels of (24S)-hydroxycholesterol in these patients.…”
Section: The Major Oxysterols In Human Circulation Are Derived From Different Pools Of Cholesterolsupporting
confidence: 81%
See 1 more Smart Citation
“…As the expression of cholesterol (24S)-hydroxylase is mainly localized to neuronal cells, and (24S)-hydroxycholesterol is mainly located in myelin, an expected consequence of active neurodegeneration would be a transient increase in the flux of (24S)-hydroxycholesterol across the blood-brain barrier. In support of this hypothesis we have observed slightly but significantly increased levels of circulating (24S)-hydroxycholesterol in a specific population of Alzheimer patients (19). In advanced neurodegeneration the decrease in neuronal mass could result in a reduced flux of (24S)-hydroxycholesterol, and we have observed a negative correlation between mental capacity and circulating levels of (24S)-hydroxycholesterol in these patients.…”
Section: The Major Oxysterols In Human Circulation Are Derived From Different Pools Of Cholesterolsupporting
confidence: 81%
“…We have suggested that plasma levels of (24 S )-hydroxycholesterol may reflect cholesterol homeostasis in the brain, and that these levels can be used as a marker for pathological and/or developmental changes in the brain (19). A prerequisite for this is, however, that the proportion of (24 S )-hydroxycholesterol in the human circulation originating from extracerebral sources is negligible.…”
mentioning
confidence: 99%
“…In addition, prior to saponification, the samples were extensively saturated with nitrogen for removal of oxygen to minimize autox idation. After saponification, 130 l phosphoric acid 50% in water (v/v) was added to neutralize the solution, followed by addition of 6 ml NaCl solution in water (9 mg/ml), according procedures for oxysterol analysis as described previously (17). After extraction with 20 ml di-chloro-methane, the bottom layer was transferred into a round bottom flask and evaporated to dryness under vacuum at 50ЊC.…”
Section: Oxyphytosterol Analysis In Serummentioning
confidence: 99%
“…At the epidemiological level, retrospective studies have shown that obesity, type 2 diabetes, cardiovascular disease and hypercholesterolemia at middle-age increase the risk for dementia at older age in humans ( Pappolla et al, 2003 ; Whitmer et al, 2005 ; Stampfer, 2006 ; Solomon et al, 2009 ; Pedditizi et al, 2016 ; Anstey et al, 2017 ; Ma et al, 2020 ; Tini et al, 2020 ; Barbiellini Amidei et al, 2021 ). In line, increased plasma and CSF levels of the cholesterol metabolite 24-hydroxycholesterol (24S-OHC) that is selectively generated in neurons, have been linked to early AD development ( Lütjohann et al, 2000 ; Papassotiropoulos et al, 2002 ; Schönknecht et al, 2002 ; Li et al, 2018 ). Cholesterol has also been shown to accumulate in mature Aβ-plaques in AD patients and APP(SW) mice ( Mori et al, 2001 ) and cholesterol levels in the brain positively correlate with the severity of dementia in AD patients ( Cutler et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%